Pre- and Post-Injection Needle Pain in Patients Undergoing First Intracavernosal Injection. Issue 4 (26th February 2022) - Baird, Bryce; Wajswol, Ethan; Ericson, Christian; Anderson, Augustus; Broderick, Gregory
ABSTRACT: Background: Intracavernosal injections (ICI) are a well-established treatment option for men with erectile dysfunction (ED); however, the anticipation of pain with injection remains a significant barrier to the use of ICI. Aim: To evaluate the patient-anticipated degree of pain versus the experienced degree of pain pre- and post-ICI in men undergoing their first injection with an erectile agent. Methods: We studied 51 patients who underwent their first ICI in our men's health clinic. Anticipated needle-associated pain was judged with a pre-injection score, and pain experienced during the injection was judged with a post-injection score. All patients graded their pre- and post-ICI pain using a standard 10-point scale (0–10). Outcomes: Pre- and post-ICI pain was defined with the visual analogue scale (0–10) in men undergoing their first penile injection. Results: Medians and interquartile ranges (IQRs) of the patients' age [65 years (54.5–68.0)], pre-injection pain [5 (4–7)], and post-injection pain [1 (1–2)] were recorded. Most men in the study had erectile dysfunction (68.6%) and/or Peyronie's Disease (64.7%). The average pre-injection prediction pain score was 5.45 ± 2.15; the average post-injection perceived pain score was 1.20 ± 0.73. Thus, there was an average discrepancy of over 4 points in predicted pain vs perceived pain. A paired t-test was performed which showed a statistically significant difference between pre- and post-injection scores ( P < .05). A Wilcoxson Signed Rank Test showed statistical significance in the difference between pre- and post-injection pain scores ( P < .05). Clinical Implications: ICI is a safe, effective treatment for patients with ED and is associated with significantly less pain than is anticipated by patients. Strengths & Limitations: This is the first report to describe the discrepancy between pre-ICI anticipated pain and post-ICI experienced pain. Limitations include an overall small sample size. Conclusion: Patients experience significantly less pain with ICI than they anticipate having. This represents an important factor to consider when counseling patients about available ED treatments.